OBESITY TREATMENT: IMPACT OF BLOOD GLUCOSE, LIPID AND NON-ANTIOBESITY DRUGS ON MUSCLE MASS - Ng, Ooi Chuan; MY, Barakatun-Nisak; NH, Zubaidah; Mukhtar, Firdaus; Chandrabose, Thanalactchumy; Daud, Sarah Syahmina (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION While obesity is often linked to excess muscle mass, emerging data reveal a paradoxical relationship between metabolic parameters and sarcopenia. This study examines the interplay between blood glucose regulation, lipid metabolism, and muscle mass retention in metabolic obesity. METHODOLOGY A cross-sectional study was conducted at Hospital Sultan Abdul Aziz Shah (HSAAS), Serdang, Selangor, to identify factors influencing muscle mass changes in metabolic obesity. Adults (≥18 years) with BMI ≥27 kg/m² and at least two comorbidities were included, while those with bariatric surgery or conditions causing intentional weight loss were excluded. Clinical data, including BMI, metabolic parameters, and medication use, were collected. Sample size was determined using a correlation formula. RESULT Among 35 individuals (BMI ≥26.5 kg/m²), hyperglycemia (HbA1c >6.5%) and hypertriglyceridemia (≥1.7 mmol/L) correlated with muscle loss, whereas normoglycemia and favorable lipid profiles (HDL ≥1.2 mmol/L, LDL <2.6 mmol/L) were protective. Moderate obesity (BMI 26.5–39.9) was universally associated with muscle gain, whereas severe obesity (BMI ≥40) showed mixed outcomes. Beta-blockers and hormones promoted muscle retention, while statins and protease inhibitors correlated with muscle decline. CONCLUSION Metabolic control, rather than BMI alone, plays a critical role in muscle retention among obese individuals. Glycemic and lipid optimization may be key in mitigating sarcopenia risk in metabolic obesity.